Recent analytical techniques, and potential eco-toxicological impacts of textile fibrous microplastics (FMPs) and associated contaminates: A review. (June 2023) - Yadav, Sangita; Kataria, Navish; Khyalia, Pradeep; Rose, Pawan Kumar; Mukherjee, Santanu; Sabherwal, Himani; Chai, Wai Siong; Rajendran, Saravanan; Jiang, Jheng-Jie; Khoo, Kuan Shiong
Abstract: Despite of our growing understanding of microplastic's implications, research on the effects of fibrous microplastic (FMPs) on the environment is still in its infancy. Some scientists have hypothesized the possibility of natural textile fibres, which may act as one of the emerging environmental pollutants prevalent among microplastic pollutants in the environment. Therefore, this review aims to critically evaluate the toxic effects of emerging FMPs, the presence, and sources of FMPs in the environment, identification and analytical techniques, and the potential impact or toxicity of the FMPs on the environment and human health. About175 publications (2011–2023) based on FMPs were identified and critically reviewed for transportation, analysis and ecotoxicological behaviours of FMPs in the environment. Textile industries, wastewater treatment plants, and household washing of clothes are significant sources of FMPs. In addition, various characterization techniques (e.g., FTIR, SEM, RAMAN, TGA, microscope, and X-Ray Fluorescence Spectroscopy) commonly used for the identification and analysis of FMPs are also discussed, which justifies the novelty aspects of this review. FMPs are pollutants of emerging concern due to their prevalence and persistence in the environment. FMPs are also found in the food chain, which is an alarming situation for living organisms, including effects on the nervous system, digestive system, circulatory system, and genetic alteration. This review will provide readers with a comparison of different analytical techniques, which will be helpful for researchers to select the appropriate analytical techniques for their study and enhance their knowledge about the harmful effects of FMPs. Graphical abstract: Image 1 Highlights: A single 6–7 kg home laundry could release ≥400, 000 microfibres. Raman and FTIR along with Stereomicroscopic are prominently used for FMPs detection. FMP particles induce fertility decline, immune deficiency, and endocrine disruption. FMPs associated pollutants could be enhanced the health risk concern and ecotoxicity. The standard guidelines, policy and regulations for the MPs need to be established.